The anxious chronicles: visualising my anxiety through acceptance commitment therapy (ACT) as well as humour and satire - Dugang, Pahang Chelsea Ro-Ann (Nanyang Technological University, 2024)
Anxiety is extremely prevalent and common for everyone, but even more so in young adults aged 18 to 26, with this period being an emotional and challenging time of our lives. This is when we go out into the real word, seeking independence and identity, managing expectations of not only our own but family and bosses, as well as balancing our responsibilities in school, work and relationships. I noticed that I myself have been facing anxiety together with my peers around me and how we often use humour in the form of sarcasm or irony to externalise and mediate our emotions. With anxiety being a majorly internal battle most often consisting of irrational worries, this project is my attempt at finding ways to externalise anxiety as a feeling, providing a new perspective through humour and lightness, as well as seeing how other people view and deal with their anxiety. All of these leading to showing people how to lessen the intensity of their feelings and not resist them, as well as forging a sense of community through showing different ways people perceive their anxiety, how it’s not a one-size-fits-all journey.